Enterprise cloud computing for non-engineers - Jones, Steve; Groom, Frank M. (CRC Press, Taylor & Francis Group, 2018)
This book provides a technical description of cloud computing technologies, covering cloud infrastructure and platform services. It also describes how cloud computing has made an impact in various industries and provides emerging technologies that are critical within each industry. Lastly, this book will address security requirements and provide the best practices in securing data.